Floral anatomy of Tristerix longebracteatus (Loranthaceae) - Lamilla, Laura-Alejandra; Robayo, Camila-Andrea; Castaño, Felipe; Marquínez-Casas, Xavier; Raz, Lauren (Revista de Biología Tropical, 2020)
Introduction: Most of the New World members of the Loranthaceae comprise a clade that corresponds to the tribe Psittacantheae. Previous studies on floral anatomy and development in this tribe have concentrated on the highly diversified subtribe Psittacanthinae, while the smaller subtribe Ligarineae has received less attention. A detailed anatomical description of Tristerix longebracteatus helps to fill this information gap. Objetive: The present research analyzes the anatomy of Tristerix longebracteatus flowers, detailing the structure of androecium and gynoecium, including megasporogenesis and microsporogenesis. Methodology: Anatomical serial sections of flowers at different stages of development were prepared, following processing with fixation techniques, incorporation in paraffin, microtome sectioning and staining with Astra-blue and basic fuchsin. Results: The large-sized flowers of Tristerix longebracteatus present a complex pattern of vascularization with 18-20 vascular bundles at the base of the inferior ovary. A group of three vascular bundles irrigate the 4-5 petals and associated stamens, and ten bundles continue through the gynoecium. The androecium is composed of four or five anthers with simultaneous microsporogenesis. The gynoecium as a single ovarian cavity with a central mamelon in which the archesporial tissue is oriented towards the style. The base of the style forms a nectary similar to that found in the sister genus Ligaria. Conclusions: The gynoecium with a single ovarian cavity and central mamelon is a condition shared by Tristerix (subtribe Ligarinae) and all the genera of the subtribe Psittacanthinae, except Tripodanthus. The base of the style forms a nectary similar to that found in the sister genus Ligaria. This type of stylar nectary is of taxonomic value for grouping species of the subtribe Ligarinae and difers from the annular nectary of subtribe Psittacanthinae.